Witaj :)
Wiemy, że [tex]\alpha \in (0;\pi)[/tex] oraz [tex]\sin\alpha =\frac{\sqrt{3}}{2}[/tex]
Korzystając z jedynki trygonometrycznej:
[tex]\large \boxed{\sin^2\alpha+\cos^2\alpha=1}[/tex]
Obliczam wartość [tex]cos^2\alpha[/tex]
[tex]\large \boxed{\sin^2\alpha+\cos^2\alpha=1\implies \cos^2\alpha=1-\sin^2\alpha}[/tex]
[tex]\large \boxed{\cos^2\alpha=1-(\frac{\sqrt{3}}{2})^2=1-\frac{3}{4}=\frac{1}{4} }[/tex]
Możemy obliczyć teraz wartość wyrażenia:
[tex]\large \boxed{\sin^2\alpha-3\cos^2\alpha=(\frac{\sqrt{3}}{2})^2-3\cdot \frac{1}{4} =\frac{3}{4}-\frac{3}{4}=0 }[/tex]
[tex]ODP.:\ \large \boxed{\sin^2\alpha-3\cos^2\alpha=0}[/tex]